Sustainable wineries through waste valorisation: A review of grape marc utilisation for value-added products. (February 2018) - Muhlack, Richard A.; Potumarthi, Ravichandra; Jeffery, David W.
Graphical abstract: Highlights: Grape marc as feedstock is evaluated for value added products. Extraction of phenolics, tartaric acid and antioxidants is presented. Thermochemical conversion technologies are considered. Biological treatments and agricultural/environmental applications are reviewed. An integrated approach for grape marc utilisation is proposed. Abstract: Grapes are one of the most cultivated fruits worldwide, with one third of total production used in winemaking. Both red and white winemaking processes result in substantial quantities of solid organic waste, such as grape marc (pomace) and stalks, which requires suitable disposal. Grape marc accounts for approximately 10–30% of the mass of grapes crushed and contains unfermented sugars, alcohol, polyphenols, tannins, pigments, and other valuable products. Being a natural plant product rich in lignocellulosic compounds, grape marc is also a promising feedstock for renewable energy production. However, despite grape marc having such potential, advanced technologies to exploit this have not been widely adopted in wineries and allied industries. This review covers opportunities beyond traditional composting and animal feed, and examines value-added uses via the extraction of useful components from grape marc, as well as thermochemical and biological treatments for energy recovery, fuel or beverage alcohol production, and specialty novel products and applications such as biosurfactants and environmental remediation. New advances in relevant technology for each of these processes are discussed, and future directions proposed at both individual producer and regional facility scales, including advanced processing techniques for integrated ethanol production followed by bioenergy generation from the spent marc.